THE EFFECT OF USING THE PEER TEACHING METHOD IN ACHIEVING SOME EDUCATIONAL OBJECTIVES FOR A NUMBER OF BOXING PUNCHE - Asst. L. Ahmed Sami Hassan; Asst. L. Taha Yousef Kareem; Asst. L. Ahmed Sadiq Niyazi (American Journals, 2023)
Recent trends have emerged in the methods of teaching physical education that allow the teacher to move from one method to another and use the appropriate ones according to need and according to the individual differences between the learners and the goal for which it is to be taught, with the aim of giving the learner a greater opportunity to make decisions in the educational process, and the peer teaching method is one of the methods Modern teaching involves a student teacher who teaches a student with a lower academic level. It is a system in which students help each other and is built on the basis that education is learner-centered, taking into account an effective learning environment that focuses on integration, where the student is fully engaged in cooperative work, and education is conducted under the supervision of the teacher, as multiple studies and research have proven the effectiveness and efficiency of the teaching method. Peers help in promoting and treating learning difficulties in general, as well as in learning social skills, or in personal qualities. Many studies have indicated encouraging results when using this method to improve the academic skills of learners, and based on the above, the importance of research is highlighted in preparing an educational program using the peer teaching method in learning some boxing grips and developing the attitude towards a boxing lesson. The research problem lies in determining the effect of using this method (peer training) on skill achievement and developing the attitudes of students of the College of Physical Education towards boxing lessons. The aim of the research is to know the effect of using the peer teaching method in developing the attitude towards studying boxing. The research hypothesis is that there are statistically significant differences between the average scores of the experimental and control groups in developing the attitude towards boxing lessons. The researchers used the experimental method to suit the research problem. The research sample was randomly selected from second-year students for the academic year 2022-2023. Through the results, the researchers reached the following conclusions:- 1The peer teaching method was better than the traditional method in terms of skill achievement.- 2The peer teaching method was better than the traditional method in developing psychological orientation.- 3Using the pairing method has a significant and effective impact on developing cognitive achievement in boxing.From the conclusions, the recommendations were:- 1Emphasis on the use of peer teaching method in teaching boxing.- 2Using the cognitive achievement test in theoretical exams in other universities and colleges.
Keywords: Peer teaching method, educational objectives, boxing punches